Polar sled dogs on the North Star (Philadelphia Evening Bulletin, 1939)
"Indian summer greeting to Polar sled dogs. Admiral Byrd's Antarctic ship North Star arrives at Navy Yard, each husky on roof of its portable 'house'." With clipping